Review on Pharmacy Informatics - Kavya, Bejavada; Ramesh, Yerikala; Chandra, Yadala Prapurna; Penabaka, Venugopalaiah (Asian Journal of Pharmaceutical Research and Development, 2025)
The development of innovative oral drug delivery systems is crucial for improving the bioavailability of poorly soluble drugs. This review focuses on lipid-based nanocarriers, including solid lipid nanoparticles (SLNs), nanostructured lipid carriers (NLCs), and lipid-polymer hybrid nanoparticles (LPHNPs). These nanocarriers have shown promise in enhancing the solubility, permeability, and bioavailability of poorly soluble drugs. SLNs, NLCs, and LPHNPs have been designed to overcome the limitations of traditional oral drug delivery systems, offering improved stability, targeted delivery, and controlled release of drugs. The applications of these nanocarriers in cancer therapy, anti-inflammatory and analgesic drugs, antiviral and antibacterial agents, and cardiovascular and neurological disorders are also discussed. Despite the advantages of these nanocarriers, challenges such as stability, regulatory considerations, and scaling up production need to be addressed.